2018
DOI: 10.1002/bse.2050
|View full text |Cite
|
Sign up to set email alerts
|

Breaking niche sustainable products into the mainstream: Organic milk and free‐range eggs

Abstract: We contribute to the existing literature on factors influencing sustainable product consumption behavior by (a) employing actual supermarket sales data from over 300 outlets in England covering up to 18 million customers, and by (b) examining two products that can both be labeled as sustainable but have very different market positions: organic milk as a typical niche product, and free‐range eggs which (based on market share) can be seen as a mainstream product. Our study has looked into the influence of factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Such phenomenon points out the attitude–behavior gap which has long been discussed in previous literature (Gifford & Sussman, 2012; Lutz, 1991; Stern, 2000), including in the domain of pro‐environmental behavior (Aschemann‐Witzel & Niebuhr Aagaard, 2014; Carrus et al, 2008; Chintakayala et al, 2018; Shin et al, 2018), which is simply called the “environmental attitude–behavior gap,” “environmental gap” (Redondo & Puelles, 2017), or “ethical purchasing gap” (Nicholls & Lee, 2006). The fact that attitudes do not always correlate to a subsequent change in behavior can be attributed to a moderator effect (Alwitt & Berger, 1993; Gifford & Nilsson, 2014; Papaoikonomou et al, 2011; Stojanova et al, 2021).…”
Section: Introductionmentioning
confidence: 66%
“…Such phenomenon points out the attitude–behavior gap which has long been discussed in previous literature (Gifford & Sussman, 2012; Lutz, 1991; Stern, 2000), including in the domain of pro‐environmental behavior (Aschemann‐Witzel & Niebuhr Aagaard, 2014; Carrus et al, 2008; Chintakayala et al, 2018; Shin et al, 2018), which is simply called the “environmental attitude–behavior gap,” “environmental gap” (Redondo & Puelles, 2017), or “ethical purchasing gap” (Nicholls & Lee, 2006). The fact that attitudes do not always correlate to a subsequent change in behavior can be attributed to a moderator effect (Alwitt & Berger, 1993; Gifford & Nilsson, 2014; Papaoikonomou et al, 2011; Stojanova et al, 2021).…”
Section: Introductionmentioning
confidence: 66%
“…There are examples of sales data at scale from loyalty card transactions in location planning research, rather than in a nutritional context, using data to predict demand in tourist destinations [ 17 ]. We have additionally seen transaction data in sustainability research investigating purchase patterns of organic and free range foods [ 18 ]. More recently research is emerging using transaction data to better understand nutrition and related health outcomes [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some companies have implemented green marketing as the main focus of business for the company (Nadanyiova et al, 2015); (Chahal et al, 2014); (Ottman et al, 2006), but there are also companies that view green marketing as only a minor marketing strategy or a niche / niche market strategy (Chintakayala et al, 2018); (Smith, 2006). The support of public policy makers by increasing attention to environmental issues, can increasingly be indicated that environmental care is a potential business area to be used as a business strategy (Peattie & Crane, 2005).…”
Section: Findings and Discussionmentioning
confidence: 99%